Modeling and Simulation on NOx and N2O Formation in Co-combustion of Low-rank Coal and Palm Kernel Shell - Mahidin, Mahidin; Gani, Asri; Khairil, Khairil (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2012)
NOx and N2O emissions from coal combustion are claimed as the major contributors for the acid rain, photochemical smog, green house and ozone depletion problems. Based on the facts, study on those emissions formation is interest topic in the combustion area. In this paper, theoretical study by modeling and simulation on NOx and N2O formation in co-combustion of low-rank coal and palm kernel shell has been done. Combustion model was developed by using the principle of chemical-reaction equilibrium. Simulation on the model in order to evaluate the composition of the flue gas was performed by minimization the Gibbs free energy. The results showed that by introduced of biomass in coal combustion can reduce the NOx concentration in considerably level. Maximum NO level in co-combustion of low-rank coal and palm kernel shell with fuel composition 1:1 is 2,350 ppm, low enough compared to single low-rank coal combustion up to 3,150 ppm. Moreover, N2O is less than 0.25 ppm in all cases.Keywords: low-rank coal, N2O emission, NOx emission, palm kernel shell